Socio economic impact, coastal land use pattern and livelihood status of Shyamnagar upazila, Satkhira, Bangladesh (Asian-Australasian Journal of Food Safety and Security, 2020)
Shyamnangar upazila one of the potential developing upazila of Satkhira district. Addressing social aspects is very important for any sorts of development effort. The best possible use of land resources; therefore, the socio-economic aspects of Shyamnangar upazila have to be addressed to gain optimum economic benefits from agriculture, forestry, fisheries, tourism and industrial sector. The socio-economic transformation of this upazila significantly depends on the performance of the agricultural sector. Besides agriculture, fisheries, tourism, industry, weaving and livestock farming are also playing vital roles in the socio-economic development of this upazila. Although this upazila has not yet been experienced in planned industrialization but, there are some small and medium industries which are contributing largely to the socio-economic development. Over the last 10 years, the socio-economic condition of the upazila is gradually rising. The growing of small & medium industries, business associated with agricultural products are the key element of socio-economic growth of Shyamnagar. Over the last 10 years, the socio-economic condition of the upazila is gradually rising. The growing of small & medium industries, business associated with agricultural products are the key element of socio-economic growth of Shyamnagar.Asian Australas. J. Food Saf. Secur. 2020, 4 (2), 31-40